(untitled) (Journal of EAHIL, 2019)
This article presents a brief overview of the literature about professional failure, impostor syndrome, perfectionism, burnout, and resilience, literature which also informed a workshop at the EAHIL Conference held in Cardiff, UK, on 12 July 2018. The workshop brought together 20 participants from across Europe who ranged in age and in career experiences. It aimed to enable participants to feel comfortable talking about and sharing their experiences of professional failure for medical or health librarians and information professionals, and drawing out solutions to those failures. This article shares the outcomes of the workshop, and includes suggestions for ways to manage professional failure.